Peran Bank Sampah Dalam Meningkatkan Pendapatan Masyarakat di Kelurahan Untia - Rusdi, Rusdi; BK, Nadita; Padli, Feri; Falihin, Dalilul (UNM Geographic Journal, 2025)
The Role of Waste Bank in Increasing Community Income in Untia Village. This research aims to find out: 1) To find out how the role of Lepa-lepa Waste Bank in increasing community income in Untia Village 2) To find out the factors that support and inhibit the Lepa-lepa Waste Bank in increasing community income in Untia Village. The type of research used is qualitative with a case study approach. The data collection techniques used in this research are observation, interview, and documentation. Data analysis used in this research is data reduction, data presentation, and conclusion drawing. The results showed that: 1) Lepa-lepa Waste Bank located in Untia Village has made a significant contribution in increasing community income. Through waste saving activities, people involved in the waste bank program earn additional income. The results of the income earned by the community are then utilized for the daily needs of the community. This shows that the Waste Bank program has begun to encourage the community to become more economically independent. Therefore, the Lepa-lepa Waste Bank through saving and sorting waste according to its type contributes to increasing community income in untia village. 2) There are factors that support and inhibit the Lepa-lepa Waste Bank in increasing community income in Untia village. Supporting factors are; member involvement, facilities and infrastructure, community involvement, and cooperation with other parties. While the inhibiting factors include customer indiscipline, low community mindset, and lack of interest   from young people.